Low-temperature fabrication of layered self organized ge clusters by RF-sputtering - Pinto, S. R. C. (2011)
In this article, we present an investigation of (Ge + SiO2)/SiO2 multilayers deposited by magnetron sputtering and subsequently annealed at different temperatures. The structural properties were investigated by transmission electron microscopy, grazing incidence small angles X-ray scattering, Rutherford backscattering spectrometry, Raman, and X-ray photoelectron spectroscopies. We show a formation of self-assembled Ge clusters during the deposition at 250°C. The clusters are ordered in a three-dimensional lattice, and they have very small sizes (about 3 nm) and narrow size distribution. The crystallization of the clusters was achieved at annealing temperature of 700°C.